Braconid wasps (Hymenoptera) of Reunion. 1. Euphorinae (including Meteorini): key to species and description of six new species - Rousse, Pascal; Braet, Yves (Zootaxa, 2012)
We revised the Euphorinae (Hymenoptera: Braconidae) collected in Reunion Island (Indian Ocean). To date, only Chrysopophthorus hungaricus (Kiss) was reported there. This catalogue is updated to a total of nine species, six of them being newly described: Centistes caloupile sp. nov., Cosmophorus merdiculus sp. nov., Leiophron sarahae sp. nov., Leiophron yaeli sp. nov., Meteorus comonile sp. nov., and Syntretus massale sp. nov. A key to all euphorine species of Reunion is provided.